Evaluating working memory in young individuals with normal hearing through tele-assessment and traditional assessment: a comparative study - Nisha, Kavassery Venkateswaran; Devi, N.; Vandana, B.; Rashmi, E.; Shende, Shraddha A.; Mudar, Raksha A. (Frontiers in Digital Health, 2025)
AimThis pilot study examined the feasibility of tele-assessment of working memory (WM) compared to conventional face-to-face assessment.MethodsIn total, 15 young adults aged between 18 and 30 years who were native speakers of Kannada with normal hearing completed three WM tests in Indian English: forward digit span, backward digit span, and n-back task through tele-assessment and in-person/face-to-face assessment. The National Aeronautics and Space Administration (NASA) task load index, which assesses subjective workload, was used to determine the difficulties across the two modes of assessment.ResultsPaired comparison t-tests showed no significant differences in performance in the forward digit span (p = 0.29), backward digit span (p = 0.71), and n-back (p = 0.66) tasks across the two assessment conditions. Furthermore, the NASA task load index did not differ across the two assessment conditions for forward digit span (p = 0.29), backward digit span (p = 0.71), and n-back (p = 0.66). The Wilcoxon signed-rank test showed that the backward digit span task was the most difficult among the working memory tasks in both modes of assessment. The findings of our pilot study suggest that both modes can be used successfully to assess working memory, and tele-assessment yields similar results to face-to-face WM assessment in young normal-hearing adults. These results support the feasibility of conducting WM tests via tele-assessment, which has implications for use in clinical populations.